Physical activity and quality of life in prostate and breast cancer patients: a comparative study - Ribovski, Marina (2018)
The objective of this study was to compare the physical activity and quality of life of patients with prostate cancer and breast cancer undergoing clinical treatment and after treatment. A cross-sectional study with 148 patients (44 men and 104 women), median age of 58.77±10.53 years old, was conduced collecting data with a questionnaire containing: general information, economic status (IBGE), physical activity (IPAQ – short version) and quality of life (EORTC QLQ-C30). The majority of the patients were classified as insufficient active (70.3%) with no difference between the two types of cancer. The time total and actual physical activity practice was 34 min/day, with the walking as the most practiced activity, with 21 min/day. The prostate cancer patients presented better functional scale as the symptomatic scale of quality of life, highlighting the worse scores for the breast cancer patients on the variables of fatigue (p=0.027), nauseas/vomits (p=0.048) and financial difficulties (p=0.034). We conclude that majority of the sample was classified as insufficient active and the prostate cancer patients presented better scores in the functional and symptomatic scales of quality of life when comparing to breast cancer patients.